The Role of Faculty Members in Promoting the Practice of a Culture of Dialogue Among Students at Al-Balqa Applied University in Jordan - AL-Momani, Mohammad Omar; Al-Friehat, Hana Mahmoud; Al-Momani, Fakhri Falah Al-Ali (Journal of Posthumanism, 2025)
The objective of the present study was to ascertain the role of faculty members in fostering a culture of dialogue among students at Al-Balqa Applied University in Jordan, from the perspective of the students themselves, and its relationship to the variables of gender and type of academic specialization. A descriptive approach was utilized in conjunction with a questionnaire comprising 15 items, which served as the study instrument. The study sample consisted of 1,245 male and female students from Al-Balqa Applied University, across its various specializations and colleges. The study concluded that the role of faculty members in promoting the practice of a culture of dialogue among students at Al-Balqa Applied University was (moderate), with an arithmetic mean of (3.27) and a standard deviation of (0.63). The findings further revealed no statistically significant disparities in the role of faculty members in fostering a culture of dialogue among students at Al-Balqa Applied University, as perceived by the students themselves, contingent on the variables of gender and academic specialization.